Wigner-molecularization-enabled dynamic nuclear polarization - Jang, Wonjin; Kim, Jehyun; Park, Jaemin; Kim, Gyeonghun; Cho, Min-Kyun; Jang, Hyeongyu; Sim, Sangwoo; Kang, Byoungwoo; Jung, Hwanchul; Umansky, Vladimir; Kim, Dohun (Nature communications, 2023)
Multielectron semiconductor quantum dots (QDs) provide a novel platform to study the Coulomb interaction-driven, spatially localized electron states of Wigner molecules (WMs). Although Wigner-molecularization has been confirmed by real-space imaging and coherent spectroscopy, the open system dynamics of the strongly correlated states with the environment are not yet well understood. Here, we demonstrate efficient control of spin transfer between an artificial three-electron WM and the nuclear environment in a GaAs double QD. A Landau–Zener sweep-based polarization sequence and low-lying anticrossings of spin multiplet states enabled by Wigner-molecularization are utilized. Combined with coherent control of spin states, we achieve control of magnitude, polarity, and site dependence of the nuclear field. We demonstrate that the same level of control cannot be achieved in the non-interacting regime. Thus, we confirm the spin structure of a WM, paving the way for active control of correlated electron states for application in mesoscopic environment engineering. Wigner molecules, or correlated localized electron states, has been reported in semiconductor quantum dots, but their interaction with environment has been less explored. Here the authors use the spin multiplet structure of a three-electron Wigner molecule to enhance and control dynamic nuclear polarization.